2018
DOI: 10.1111/1751-7915.13358
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic research in neonates with congenital gastrointestinal surgical conditions – Now is the time

Abstract: Summary Neonates with congenital gastrointestinal surgical conditions ( CGISC ) receive parenteral nutrition, get exposed to multiple courses of antibiotics, undergo invasive procedures, and are nursed in intensive care units. They do not receive early enteral feeding and have limited opportunities for skin to skin contact with their mothers. Many of these infants receive gastric acid suppression therapies. All these factors increase the risk of gut dysbiosis in these infants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Probiotics are known to inhibit gut colonization with pathogenic bacteria enhance gut barrier function, facilitate colonization with healthy commensals, protect from enteropathogenic infection through production of acetate, reduce antimicrobial resistance, enhance innate immunity and increase maturation of the enteric nervous system and promote gut peristalsis. 32 Through these mechanisms, probiotics have the potential to decrease the risk of sepsis, improve feed tolerance and minimize parenteral nutrition-associated cholestasis in infants with CGISCs. 32 Meta-analyses of RCTs in preterm infants (non-surgical) have shown probiotic supplementation to be beneficial in decreasing mortality, necrotizing enterocolitis (NEC), late-onset sepsis and improving feed tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are known to inhibit gut colonization with pathogenic bacteria enhance gut barrier function, facilitate colonization with healthy commensals, protect from enteropathogenic infection through production of acetate, reduce antimicrobial resistance, enhance innate immunity and increase maturation of the enteric nervous system and promote gut peristalsis. 32 Through these mechanisms, probiotics have the potential to decrease the risk of sepsis, improve feed tolerance and minimize parenteral nutrition-associated cholestasis in infants with CGISCs. 32 Meta-analyses of RCTs in preterm infants (non-surgical) have shown probiotic supplementation to be beneficial in decreasing mortality, necrotizing enterocolitis (NEC), late-onset sepsis and improving feed tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…32 Through these mechanisms, probiotics have the potential to decrease the risk of sepsis, improve feed tolerance and minimize parenteral nutrition-associated cholestasis in infants with CGISCs. 32 Meta-analyses of RCTs in preterm infants (non-surgical) have shown probiotic supplementation to be beneficial in decreasing mortality, necrotizing enterocolitis (NEC), late-onset sepsis and improving feed tolerance. 33 Majority of the RCTs included in those meta-analyses used Bifidobacteria as the sole or one of the components of probiotic supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that probiotic supplementation attenuates gut dysbiosis, strengthens the gut barrier, prevents enteropathogenic infections, reduces antimicrobial resistance, enhances immunity, and promotes gut peristalsis. 16 Through these mechanisms, probiotics have the potential to improve the outcomes of neonates with CGISC. 16 Many beneficial biological functions of probiotics are mediated via short-chain fatty acids (SCFAs).…”
Section: Introductionmentioning
confidence: 99%
“… 16 Through these mechanisms, probiotics have the potential to improve the outcomes of neonates with CGISC. 16 Many beneficial biological functions of probiotics are mediated via short-chain fatty acids (SCFAs). 17 The major SCFAs (80–95%) in the gut are acetate, propionate, and butyrate.…”
Section: Introductionmentioning
confidence: 99%